Effect of Cotton Stalk Biochar Content on the Properties of Cotton Stalk and Residual Film Composites - Zhipeng Song; Xiaoyun Lian; Junhui Ran; Xuan Zheng; Xufeng Wang; Xiaoqing Lian (Agriculture)
This study aims to improve the performance of wood–plastic composites (WPCs) composed of cotton stalk powder and residual film particles. Additionally, it aims to promote the efficient utilization of cotton stalk biochar. The composites were prepared using modified cotton stalk biochar and xylem powder as the matrix, maleic anhydride grafted high-density polyethylene (MA-HDPE) as the coupling agent, and polyethylene (PE) residual film particles as the filler. The WPCs were fabricated through melt blending using a twin-screw extruder. Mechanical properties were evaluated using a universal testing machine and texture analyzer, Shore D hardness was measured using a durometer, and microstructure was analyzed using a high-resolution digital optical microscope. A systematic investigation was conducted on the effect of biochar content on material properties. The results indicated that modified biochar significantly enhanced the mechanical and thermal properties of the WPCs. At a biochar content of 80%, the material achieved optimal performance, with a hardness of 57.625 HD, a bending strength of 463.159 MPa, and a tensile strength of 13.288 MPa. Additionally, thermal conductivity and thermal diffusivity decreased to 0.174 W/(m·K) and 0.220 mm2/s, respectively, indicating improved thermal insulation properties. This research provides a novel approach for the high-value utilization of cotton stalks and residual films, offering a potential solution to reduce agricultural waste pollution in Xinjiang and contributing to the development of low-cost and high-performance WPCs with wide-ranging applications.